Research on nonlinear dynamics of giant magnetostrictive actuators under delayed feedback control - YAN Yan; GAO Daxiao (Jixie chuandong, 2025)
ObjectiveIn response to the bifurcation and chaos phenomena in the dynamics of giant magnetostrictive actuator (GMA), which reduce the output stability of the system, a velocity delay feedback controller was designed to suppress the main resonance bifurcation and chaotic motion of the GMA system.MethodsThe analytical expression and amplitude frequency response equation of the system were solved based on the multi-scale method. The influence of the key structural parameters of the system and the delayed feedback parameters on the main resonance and chaotic motion of the system was studied through the numerical simulation.ResultsThe research results indicate that appropriately increasing the feedback gain coefficient and reducing the delay parameter can effectively eliminate the main resonance bifurcation phenomenon of the system. Increasing the feedback gain coefficient can adjust the system response from chaotic motion to periodic motion, thereby improving the stability of the system.